2022
DOI: 10.3390/su142416920
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Complexity between Boredom and Engagement in English Learning: Evidence from Chinese High School Students

Abstract: Although boredom is a negative emotion that students frequently experience in the process of learning English, boredom in language learning has received scant research attention in terms of its structure, levels and impact on language learning engagement. To fill this gap, the study focused on data obtained from 1157 high school students in six different areas of mainland China via a questionnaire. Exploratory factor analysis revealed a binary structure of English learning boredom (ELB) and a tri-structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…However, more evidence is needed to draw robust conclusions regarding EFL learners' engagement. This is evident from the mixed results of Lin (2020) study, which found moderate engagement among EFL learners in Taiwan, and Liu et al (2022) findings indicating medium to high engagement among EFL learners in the Chinese mainland.…”
Section: Efl Learners' Academic Engagementmentioning
confidence: 96%
“…However, more evidence is needed to draw robust conclusions regarding EFL learners' engagement. This is evident from the mixed results of Lin (2020) study, which found moderate engagement among EFL learners in Taiwan, and Liu et al (2022) findings indicating medium to high engagement among EFL learners in the Chinese mainland.…”
Section: Efl Learners' Academic Engagementmentioning
confidence: 96%
“…Regarding the inner structure of the construct of boredom, Pawlak, Kruk, et al's (2020) study was a pioneering attempt to uncover the complex nature of this negative emotion. Their specific focus on Polish EFL university learners unveiled a two-dimensional structure of boredom, that is, insufficient challenge and stimulation and avoidance and disinterest in foreign language learning (H. Liu et al, 2022). Their contribution paved the way for further investigation of this variable.…”
Section: Typologies and Multidimensionality Of Efl Classroom Boredommentioning
confidence: 99%
“…Among these related studies, emotions, such as enjoyment (Li, 2020;G.-Z. Liu et al, 2024) and anxiety (e.g., H. Liu et al, 2023), have been widely investigated, with boredom remaining underexplored (e.g., H. Liu et al, 2022;Wang & Liu, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A strong sense of belonging has been associated with positive outcomes, such as higher academic achievement and lower rates of dropout [55]. Sense of belonging has also been found to be positively correlated with academic curiosity [10,11].…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies have investigated the mediating role of personality traits in the relationship between sense of belonging and academic curiosity. For instance, [55] found that openness to experience mediated the relationship between sense of belonging and academic curiosity in Chinese college students. Similarly, Chen et al [56] found that conscientiousness and openness to experience mediated the relationship between sense of belonging and academic curiosity in Chinese high school students.…”
Section: Introductionmentioning
confidence: 99%